Changes in cardiac anxiety and self-care practices in heart failure patients following implantation of wireless hemodynamic monitoring sensors. (1st June 2020) - Sager, David M; Burch, Ashley E; Alhosaini, Hassan; Vaughan, Tracy; Sears, Samuel F
Abstract: Background: Wireless implantable hemodynamic monitors assist cardiac care providers in tailoring medication regimens to reduce chronic heart failure hospital admissions and to improve patient quality of life. Previous research exists to support wireless implantable hemodynamic monitors favorable impact on medical endpoints but, however, their psychological and behavioral effects have not yet been established. The purpose of this pilot study was to investigate patient psychological and behavioral changes after receiving the wireless implantable hemodynamic monitor. Methods: Patients with heart failure ( n =26) who were implanted with wireless implantable hemodynamic monitor sensors completed the Cardiac Anxiety Questionnaire and Self-Care of Heart Failure Index version 6.2 at pre-implant and at one-month post-implant, as well as an initial demographic questionnaire. Results: Heart failure patients who received a wireless implantable hemodynamic monitor experienced a significant reduction in cardiac anxiety, t (25)=2.93, p =0.007, z =−0.46, d =0.58, driven by a reduction in fear of their condition, t (25)=2.26, p =0.03, z =−0.42, d =0.44. Increases in self-care behaviors fell short of significance t (25)=1.67, p =0.11, but showed a medium effect size, d =0.33. Conclusion: Heart failure patients who received a wireless implantable hemodynamic monitor reported significantly reduced cardiac fear, indicating that wireless implantable hemodynamic monitor technology may produce a collateral benefit in psychological effects. Patient self-care may also benefit but the current study was under-powered to reach statistical significance. Patient education about psychological and behavioral aspects of the wireless implantable hemodynamic monitor implant may yield increased patient engagement and broader health benefits if these results are confirmed in a larger study.